2021
DOI: 10.3390/cancers13081979
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Pharmacological or Hospital Treatment for Depression in Patients with Colorectal Cancer–Associations with Pre-Cancer Lifestyle, Comorbidity and Clinical Factors

Abstract: We investigated the risk of depression in colorectal cancer (CRC) patients and associated risk factors. The 1324 patients with CRC and 6620 matched cancer-free participants from the Diet, Cancer and Health study were followed for up to 16 years for either a first hospitalization for depression or antidepressant prescription after diagnosis of CRC cancer or study entry date. Information on the outcome and covariates was retrieved from the Danish Colorectal Cancer Group database, the national health registries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Out of the included studies, six studies [ 6 , 8 , 17 , 18 , 19 , 20 ] assessed both anxiety and depression, and two studies [ 7 , 21 ] assessed depression only. Included studies were predominantly conducted in developed countries: United States ( n = 3) [ 6 , 17 , 21 ], Taiwan ( n = 2) [ 18 , 20 ], Netherlands ( n = 1) [ 19 ], Denmark ( n = 1) [ 7 ], and Canada ( n = 1) [ 8 ]. All studies used administrative health data from their respective countries as their main data source.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of the included studies, six studies [ 6 , 8 , 17 , 18 , 19 , 20 ] assessed both anxiety and depression, and two studies [ 7 , 21 ] assessed depression only. Included studies were predominantly conducted in developed countries: United States ( n = 3) [ 6 , 17 , 21 ], Taiwan ( n = 2) [ 18 , 20 ], Netherlands ( n = 1) [ 19 ], Denmark ( n = 1) [ 7 ], and Canada ( n = 1) [ 8 ]. All studies used administrative health data from their respective countries as their main data source.…”
Section: Resultsmentioning
confidence: 99%
“…However, we note that, although studies were assessed to be reporting sex, as generally administrative health data do not capture gender, sex and gender terminology were conflated in half of the studies ( n = 2) [ 17 , 21 ], where the terms ‘men’ and ‘women’ (which refer to sex) were used interchangeably with ‘males’ and ‘females’ (which refer to gender), respectively. In regard to age, the majority of studies ( n = 7) [ 6 , 8 , 17 , 18 , 19 , 20 , 21 ] reported the age at the time of CRC diagnosis and one study [ 7 ] reported age at the time of the study. However, all studies varied in their reporting of age, as we observed either the reporting of mean and standard deviation or proportion according to varying age categories.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identified risk factors were presence of comorbidities, advanced disease stage and use of radiotherapy, while lifestyle factors and chemotherapy did not seem to contribute to the increased risk. Care professionals should be aware of this late effect of CRC and its treatments, particularly in patients with comorbid conditions, advanced disease stage and patients who are treated with radiotherapy [ 13 ].…”
mentioning
confidence: 99%